Majālis - Tabrīzī, Jalāl al-Dīn ʿAtīqī (Miras Maktoob, ISBN: 9789004365452., 2019)
Rashīd al-Dīn Hamadānī (d. 718/1319) came from a Jewish family in Hamadan. His grandfather had been a courtier of Hūlāgū Khān (r. 1256-65) while his father was a court pharmacist. Rashīd al-Dīn converted to Islam when he was about 30 years old. Trained as a physician, he started his career under the Il-khanid Abāqā Khān (r. 1265-82), rising to the rank of vizier under Ghāzān (r. 1295-1304), Öljeitü (r. 1304-16) and Abū Saʿīd Bahādur Khān (r. 1316-35) who had him executed in 718/1319. Rashīd al-Dīn is the author of the first world history ever, the Jāmiʿ al-tawārīkh . Besides he also wrote a considerable number of texts on many different subjects. As a promotor of learning, Rashīd al-Dīn founded a cultural complex called the Rabʿ-i Rashīdī. Among the people invited there was the author of the present series of lectures on Sufism. Held seasonally between 712/1312 and 718/1318, these lectures survive thanks to an attentive student.